Survey of Screw-Retained versus Cement-Retained Implant Restorations in Saudi Arabia - Alaa Makke; Abdulwahed Homsi; Montaha Guzaiz; Abdulrahman Almalki (International Journal of Dentistry)
Introduction. Implant-supported prostheses are currently the standard treatment for the replacement of missing teeth and deficiencies. Implant restorations can either be screw-retained, cement-retained, or both. The implant retention system type is typically chosen during the treatment plan. The primary purpose of this study is to investigate the frequency of implant restoration retention systems. Materials and Methods. A five-page questionnaire was sent to private institutes, educational institutes, and governmental hospitals that provide dental services. The data were analyzed using descriptive statistics. Results. Prior to distribution, the surveys were proofread and pilot-tested at the Faculty of Dentistry at Umm Al-Qura University. The surveys were mailed to three groups: private institutes, educational institutes, and governmental hospitals. In total, 120 surveys were distributed and 87 surveys were returned, for a response rate of 73%. This included thirty-six surveys (41.4%) from private institutes, twenty-two surveys (25.3%) from educational institutes, and twenty-nine surveys (33.3%) from governmental hospitals. Conclusions. In general, Astra was cited as the most widely used implant system. In addition, cement-retained restorations were more frequently used than screw-retained restorations. However, dental implant failure was more frequently associated with cement-retained restorations than with screw-retained restorations.